“PERRENG KELES (PEMBERIAN AIR REBUSAN REBUNG BAMBU MUDA UNTUK MENURUNKAN HIPERTENSI DAN KOLESTEROL)” - Ahied, Moch.; Lutfi, Mohammad; Mayangsari, Mulia; Zuryaty, Zuryaty (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2024)
High levels of cholesterol in the blood is a serious problem because it is a risk factor for various non-communicable diseases, one of which is high blood pressure or hypertension, which is a health condition that is often encountered and can cause various serious complications if not treated properly. One effective way to manage and reduce high blood pressure is through diet management. Excessive cholesterol levels in the blood will easily stick to the inner walls of blood vessels. Excess LDL through the oxidation process will form clots which, if the clot gets bigger, will form lumps which will result in narrowing of the blood vessels. This process is usually called atherosclerosis. Atherosclerosis is the process of narrowing of blood vessels by fat and atherosclerosis is a clinical manifestation of heart disease. , the heart will work hard to pump blood, the result can be hypertension. Apart from that, hypertension also causes heart problems, kidney problems and retinopathy. This will be dangerous if not controlled properly. Non-Communicable Diseases (NCDs) are a health problem that has become a national and global concern. NCD morbidity and mortality is increasing in Indonesia. The results of a preliminary study conducted on the community in Masaran Village, Tragah Bangkalan District, out of 10 respondents, 5 respondents experienced hypertension and cholestrolemia with a total percentage (50%) of respondents, then 3 respondents experienced hypertension without hypercholesterolemia with a total percentage of (30%) of respondents and 2 people experienced cholesterol disease with a percentage of (20%) respondents, meaning that in this area there are still many people who experience hypertension and cholestrolemia. Indonesia's flora is very diverse in number and has quite large potential. One of the functional food ingredients made from local ingredients that has been used by the community as food and medicine and is thought to be able to inhibit the progression of atherosclerosis is bamboo shoots. In Bangkalan, especially in Masaran village, sub-district. Taragah, this young bamboo stem is often used as a cooking ingredient in making vegetables. Not only is it delicious to eat, young bamboo stems also have health benefits. The benefits of young bamboo stems are none other than the substances they contain. The high antioxidant, potassium and fiber content in bamboo shoots can help reduce bad cholesterol levels in the body without reducing the amount of good cholesterol. Bamboo shoots also contain protein, carbohydrates, vitamin A, vitamin B6, vitamin E and 12 types of amino acids which are very useful for body health. The antioxidants in bamboo shoots are like vitamins. This type of antioxidant can help reduce bad cholesterol levels in the body without reducing the amount of good cholesterol. The antioxidants in bamboo shoots are also able to protect cells from damage. Apart from that, the protein content in it will also help cells stay healthy. Apart from that, the high potassium and fiber content in bamboo shoots can also reduce blood cholesterol levels. Potassium levels can also reduce blood pressure to the heart because it can reduce pressure on blood flow, so it can maintain heart health and reduce the risk of coronary heart attacks and strokes. Even though bamboo shoots contain many benefits, until now only a few people know the benefits and consume them and there is a lack of scientific information regarding their application to humans. One of the functional food ingredients made from local ingredients that has been used by the community as food and medicine and is thought to be able to inhibit the progression of atherosclerosis is bamboo shoots. The high content of antioxidants, potassium and fiber in bamboo shoots can help reduce cholesterol levels and blood pressure (hypertension). ). In this regard, this research aims to see the effect of bamboo shoot content in reducing cholesterol levels and blood pressure. So we are interested in raising this theme, 'Perreng Keles (Giving Water Boiled from Bamboo Shoots to Reduce Hypertension and Cholesterol) in Masaran Village, District. Tragah District. Bangkalan, as our service to the community.